2012
DOI: 10.1016/j.gaitpost.2011.11.030
|View full text |Cite
|
Sign up to set email alerts
|

Gait symmetry and velocity differ in their relationship to age

Abstract: Measurement of gait is essential for identifying underlying deficits contributing to gait dysfunction, guiding clinical decisions and measuring rehabilitation outcomes. Velocity is commonly used to measure gait, however, its interpretation in patient populations is complicated by the confound of age. Gait symmetry may be an additional and valuable measure since it may not feature the same age-related changes as velocity. The purpose of this study was to determine if gait symmetry is related to age. METHODS Sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
67
3
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 89 publications
(82 citation statements)
references
References 24 publications
3
67
3
3
Order By: Relevance
“…Contrary to study results of nonsignificant effect over a continuous age range [4,24,48], some studies with significant effects [36,37] compared two different age groups. Meanwhile, Himann et al showed that gait function remains unchanged until the age of 60, which then varies greatly [58].…”
Section: The Effect Of Age On Gait Symmetrymentioning
confidence: 86%
See 3 more Smart Citations
“…Contrary to study results of nonsignificant effect over a continuous age range [4,24,48], some studies with significant effects [36,37] compared two different age groups. Meanwhile, Himann et al showed that gait function remains unchanged until the age of 60, which then varies greatly [58].…”
Section: The Effect Of Age On Gait Symmetrymentioning
confidence: 86%
“…However, studies have reported different results. Although several studies have shown that age is not effective on gait symmetry [4,6,24,48], recent studies have reported otherwise, which seems to differ in the age distribution of subjects [20,36,37].…”
Section: The Effect Of Age On Gait Symmetrymentioning
confidence: 88%
See 2 more Smart Citations
“…The mean age was 58.5 (±9.47) years. The relatively wide age range does not play a significant role in gait symmetry ratios [29]. The time since the onset of stroke varied from 6-43 years.…”
Section: Participantsmentioning
confidence: 97%